Gender Relations in Negotiating the Roles of Husbands and Wives in Career Women in the Era of Flexible and Remote Work - Magefirah; Nur Azzahra; Kurniati (PT. Nawa Edukasi Nusantara, 2026)
The transformation of digitally-based work systems and the emergence of flexible working patterns after the COVID-19 pandemic present new opportunities and dilemmas for working women. On the one hand, flexibility in working hours and locations provides women with the space to balance their professional careers and domestic responsibilities. However, on the other hand, entrenched patriarchal norms mean that they continue to bear a double burden. This study aims to reveal the mechanisms of role negotiation between husbands and wives in families where the wife has a career in the context of flexible and remote work. This study uses a phenomenological qualitative approach with data collection techniques through literature study, document analysis, and observation of developing social dynamics. The results show that remote work encourages a more equal division of roles, both in household responsibilities and emotional support between spouses. However, traditional gender norms remain a major obstacle, causing women to often face psychological and social pressure. Education and gender awareness have been proven to influence a couple's ability to adapt. This study emphasizes the need for policies that promote gender equality in flexible work systems as an effort to achieve a balance of roles in modern families.